Perkiraan Pemakaian dan Kebutuhan Beban Energi Listrik Rayon Juwana Menggunakan Jaringan Saraf Tiruan (Radial Basis Function) - Fitriyan, Moh Tamam Edy; Heranurweni, Sri; Harmini, Harmini (Universitas Semarang, 2021)
Along with the development of the times the need for electrical energy is increasing. PT. PLN (Persero) as a company that supplies electrical energy must be able to meet the needs of electrical energy to run a business to supply electric power in an even amount to meet the needs of the household, industrial, social and business sectors.. The purpose of this research to determine how much the growth of electrical loads in 2020 to 2025 at PT. PLN (Persero) Rayon Juwana. To find out the amount of increase in electrical energy required. Electrical data used data for 8 years, from 2012 to 2019. The results of this study are in the form of an estimate of the use and need for load electrical energy load for the next 5 years, from 2020 to 2025, the data used are the number of subscribers, connected power, and the amount of energy using a simulated neural network with the method (radial basis function). the results of this study an increase per year an average of 1% per year. in 2019 the value is 1.07%, in 2020 it is 1.10%, 2021 is 1.21%, for 2022 it is 1.27%, 2023 is 1.28%, 2024 is 1.17% and 2025 is 1.31 %.